1999
DOI: 10.1042/cs0970193
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sleep/wake disorders in persons with blindness

Abstract: Blind individuals are not only handicapped by their loss of vision, but are also affected because the loss of sight may have a secondary impact on functioning of their biological clock. The objective of the present study was to determine the impact of visual loss on sleep/wake disorders. A prospective 48-item questionnaire survey was distributed to blind individuals through the French Association Valentin Haüy, which serves blind persons. A control group matched by age, sex, geographical location and professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
2
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 15 publications
0
46
2
3
Order By: Relevance
“…13,14 One study has reported a PSQI ‡ 5.5 in 48.7% of subjects with visual acuity < 20/200 or a visual field of < 5°. 15 In other studies, the prevalence of sleep disorders in visually impaired people has been reported to be 58% 16 and 23%-47%, 17 depending on the sleep disorder scales and definitions of visual disorder used. The induction of sleep disorders due to disruption of the circadian rhythm is common in older people.…”
Section: Discussionmentioning
confidence: 98%
“…13,14 One study has reported a PSQI ‡ 5.5 in 48.7% of subjects with visual acuity < 20/200 or a visual field of < 5°. 15 In other studies, the prevalence of sleep disorders in visually impaired people has been reported to be 58% 16 and 23%-47%, 17 depending on the sleep disorder scales and definitions of visual disorder used. The induction of sleep disorders due to disruption of the circadian rhythm is common in older people.…”
Section: Discussionmentioning
confidence: 98%
“…Underexposure to natural bright light may disturb sleeping and waking patterns of humans, particularly for blind subjects [9]. In a previous study, we interviewed 1073 blind subjects with the help of Braille questionnaires and we found that blind subjects had significantly more insomnia and free running sleep-wake patterns than seeing controls [10,11].…”
Section: Introductionmentioning
confidence: 96%
“…16 These findings are consistent with reports by Bellastella and Leger, who reported that blind people with varying degrees of light perception are shorter in stature and have a lower BMI than sighted controls. 2,3,17 The increased current BMI in NPL women does not account for the earlier menarche observed in this group, as could be hypothesized, 18 as their weight and BMI were significantly lower than LP women at age 18. Consistent with prior reports, we found no differences between LP and NPL women in age at natural menopause, which occurred around age 50.…”
Section: Discussionmentioning
confidence: 58%
“…Consistent with prior reports, we found no differences between LP and NPL women in age at natural menopause, which occurred around age 50. 17 We also found no differences in the age of first birth between LP and NPL women; however, only 42% of NPL women reported being parous compared to 57% of LP women.…”
Section: Discussionmentioning
confidence: 65%